PODCAST SEBAGAI STRATEGI DAKWAH DI ERA DIGITAL: ANALISIS PELUANG DAN TANTANGAN - Ummah, Athik Hidayatul; Khairul Khatoni, M.; Khairurromadhan, M. (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2020)
Digital da'wah is a new demand and trend currently, because public especially the younger generation search religious knowledge through new media. Podcasts are one of the most popular new media because flexible and can be accessed on various platforms. This study aims to analyze the opportunities and challenges, and Podcast strategy model as an effective digital da'wah media. The research method is library research to analyze various literature with in-depth analysis to answer the research problems. The results showed that Podcast is an effective digital da'wah media because it can transform religious knowledge to the public; can be collaborated with other media; alternative media to disseminate audio content individually or institutionally; can be accessed safely and comfortably. The strategies to manage digital da'wah through Podcasts are identify characteristics of the da'wah object, create an interesting message of preaching, use the appropriate da'wah methods, and use the media according to the target.